Eutanasia, suicidio asistido y derechos humanos: un estudio de jurisprudencia comparada - Buriticá-Arango, Esteban (2023)
Judges have played a leading role in the decriminalization of euthanasia and assisted suicide in several countries. Since the 1990s, they have promoted the annulment or restriction of norms that punish mercy killing and assisted suicide and have contributed to the development of the ethicallegal foundations of assisted death procedures. However, in each country, the judges have attributed very different scope, nature and foundations to the right to assisted death. In this article I analyze three main differences, related to the conditions that give access to medical care, the fundamental rights that support it and its nature as a subjective right. I conclude that the right to assisted death can be, depending on the country, a privilege, an immunity or a claim, often based on different—and incompatible— interpretations of fundamental rights and with variable applicability.